THE EFFECT OF IRON SUPPLEMENTATION AND OTHER SCHOOL-BASED SUPPORT ON ANEMIA STATUS IN ADOLESCENTS: A SYSTEMATIC LITERATURE REVIEW - Zahiroh Amani; Susy Katikana Sebayang (Indonesian Midwifery and Health Sciences Journal)
Background: Anmia among adolescent girls is still problematic. The 2018 RISKESDAS Indonesia survey revealed that anemia among pregnant women was linked to the high prevalence of anemia among adolescents (25%) and women of reproductive age (17%). School support is considered important to help overcome the problem of anemia among adolescent girls. This research aims to assess the effectiveness of school support in providing iron supplements and other support for anemia status in adolescents. Method: This was Systematic Literature Review of publications found on Google Scholar and Pubmed databases using the following inclusion criteria: published in Indonesian or international journals between 2018 – 2023 and written in Bahasa Indonesia or English. The article search utilized the following keywords on Google Scholar: "dukungan sekolah dan tablet tambah darah dan status anemia remaja dan kepatuhan" and "dukungan sekolah dan ttd dan status anemia remaja dan kepatuhan". The keywords used on PubMed were: "school AND (iron OR fe) AND suppl* AND (teen* OR adolescent*) AND (anemia OR anaemia)". The search for publications using these keywords in the databases resulted 1593 articles. Then, all articles entered the screening stage based on title relevance, duplicate articles, abstract, and full text access. Five articles were found to be eligible for review. Result: From the five articles obtained, the results showed that the provision of iron supplements coupled with health education and counseling about anemia in schools can reduce the risk of anemia in adolescents by 16%-48%. Both supports are considered effective in overcoming the problem of anemia among adolescent girls. Conclusion: Providing iron supplements coupled with health education and counseling about anemia at school can reduce the risk of anemia in adolescent girls.